A comparative study of the explosion behaviors of H2 and C2H4 with air, N2O and O2. (January 2021) - Wang, Lu-Qing; Ma, Hong-Hao; Shen, Zhao-Wu; Pan, Jun
Abstract: Explosions can occur in different oxidizer atmospheres in confined spaces, which should be given attention in regard to the fire safety in process industries. In this study, experiments were carried out in a closed cylindrical vessel (7.3 L) to compare the explosion behaviors of hydrogen (H2 ) and ethylene (C2 H4 ) with air, nitrous oxide (N2 O), and oxygen (O2 ) at various equivalence ratios. The initial pressures of the hydrogen and ethylene mixtures were 50 kPa and 30 kPa, respectively. Explosion indices such as the maximum explosion pressure ( P m a x ), maximum rate of pressure rise ( ( d p / d t ) m a x ) and deflagration index ( K G ) were determined experimentally. The results showed that the pressure evolutions obtained with N2 O and O2 exhibited strong oscillations due to flame instabilities and cellular structures. The maximum explosion pressure increased in the order of air, O2 and N2 O while the maximum rate of pressure rise increased in the order of air, N2 O and O2 . Unlike those of air and O2, the maximum values of ( d p / d t ) m a x obtained with N2 O were found to be at the fuel-lean side. This indicated that the instability feature of N2 O supported combustions at the fuel-lean side. Compared with air, the maximum explosion pressure obtained in N2 O and O2 atmospheres could be very close to the adiabatic pressure when considering no heat loss during an explosion. Therefore, there was a flame acceleration and deflagration to detonation transition (DDT) mechanism in the explosions with N2 O and O2 . Additionally, two dimensionless pressure rise coefficients were derived and discussed. The flames in very lean H2 -N2 O were very unstable, resulting in scattered coefficients as a function of equivalence ratio. At the fuel-rich side, the dimensionless coefficients were very close. In practice, the potential DDT mechanism in the explosions, especially in N2 O and O2 atmospheres, needed to be considered.